Becoming organic : nature and agriculture in the Indian Himalaya - Galvin, Shaila Seshia (New Haven : Yale University Press, 2021)
A rich, original study of the social and bureaucratic life of organic quality that challenges assumptions of what organic means.
Frontmatter -- Contents -- Acknowledgments -- List of Abbreviations -- Introduction: Remaking the Agrarian on a Himalayan Frontier -- ONE. Fertile Ground -- TWO. The Limits of Transparency and the Farming of Trust -- THREE. Becoming Basmati -- FOUR. Market Imaginaries and the Horizons of Aspiration -- FIVE. Exhibiting Organic Uttarakhand -- Epilogue: Promises of Transformation -- Notes -- Glossary -- Bibliography -- Index
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (De Gruyter, viewed on April 29, 2021).
JSTOR
Keywords: Organic farming -- India; Organic farming -- Himalaya Mountains Region; Agriculture and state -- India; Agriculture and state -- Himalaya Mountains Region; Agriculture biologique -- Inde; Agriculture biologique -- Himālaya.; Politique agricole -- Inde; Politique agricole -- Himālaya.; Technology & Engineering / Agriculture / Organic; Agriculture and state; Organic farming; Himalaya Mountains Region; India